EVENT MARKETING STRATEGY IN DEVELOPING THE BRAND IMAGE OF MIDEA ELECTRONICS THROUGH THE EVENT “MIDEA BUY WIN FLY 2.0” - Tazkia Nursina; Indah Fajar Rosalina; Wina Puspita Sari; Abdul Kholik; Anggun Nadia Fatimah (Indonesian Journal of Islamic Communication, 2025)
This study examines how Midea Electronics' "Buy Win Fly 2.0" event enhanced brand image through experiential marketing, using qualitative methods including interviews to analyze how entertainment, excitement, and enterprise elements shaped consumer perceptions. Findings reveal the event successfully created emotional connections through interactive games, international trip prizes, and nationwide activations featuring Manchester City collaborations, strengthening Midea's identity as an innovative and trustworthy brand while driving immediate sales and long-term loyalty. The program demonstrated event marketing's superiority over traditional advertising in building consumer relationships through immersive activities that fostered personal engagement, high-value rewards generating word-of-mouth promotion, and strategic partnerships reinforcing global positioning. The study provides actionable insights for electronics brands to design memorable experiences, leverage emotional triggers, and integrate online-offline touchpoints, while recommending future events incorporate digital extensions and sustainability themes to engage younger demographics, ultimately contributing to understanding how experiential marketing drives brand perception in competitive industries.